(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-188-200 Written in 1690 in Latin, T. Peucer’s dissertation ’De Relationibus Novellis’ was little known to the wide academic community beyond its title until 2000, when it was translated into English and published by the group of scholars from the Potchefstroom University, South Africa. A careful reading of Peucer’s dissertation demonstrates several interesting features, the most notable of which are the insignificant interest of its author to newspapers and the lack of a clear distinction between history and news. Key words: news, history, Tobias Peucer, history of journalism